Party autonomy over jurisdiction clause in Islamic Finance (Journal of Business Management and Accounting, 2011)
The principle of party autonomy is recognized internationally when it comes to the confl ict of laws. The parties are free to insert the governing law clause in their respective contract. Shamil Bank of Bahrain v. Beximco Pharmaceuticals sent repercussion to the Islamic fi nance industry when the court of England applied English law instead of what has been written in the contract i.e. â€œSubject to the principles of the Glorious Shariah, this Agreement shall be governed by and construed in accordance with the laws of England.â€. Under the party autonomy rule, it is clear that the contracting parties are allowed to nominate one legal system to govern the contract and to specify that another system be used to interpret it and in Re Helbert Wagg it was held that â€˜the parties may well contemplate that different parts of their contract shall be governed by different lawâ€™. Is there any justifi cation to exclude the intended terms of the agreeing parties in the contract and merely apply English law for the execution of the contract and to be considered as valid and name it as a proper law. In the absence of any specifi c laws governing Shariah laws in Islamic finance for international contract, the proper law is the law which is more convenient to both parties and adherence of Shariah principles. The purpose of this short article is to determine whether the concept of party autonomy rule is being upheld seriously by the English court. It also examines if the parties are free to choose a system of law unconnected with the transaction in the light of the Rome Convention and whether it is proper for the court to apply English law when the parties have consensus ad idem agreed to the terms of the contract. In addition to this, there is no generally applicable connecting factor that can be used in English law to determine the proper law of the contract. It conceptualizes the reality of the challenge when it reaches the Islamic fi nance business fraternity across borders.